Basin efficiency approach and its effect on streamflow quality, Zerafshan River Uzbekistan - Olsson, O.; Gassmann, M.; Manig, N.; Ikramova, M.; Wegerich, Kai (Elsevier, 2013)
Understanding the spatial-temporal patterns of water quality parameters and apportioning the sources of water pollution are important for water management. Within the Zerafshan basin a basin efficiency approach is practiced. Here water quality data for a 30 year period are presented and analysed according to spatial distribution utilising box plots and cluster analysis. The results show quality declines in its middle and lower reaches due to return flows from intensively irrigated agricultural region as well as a ''Hot spot'' with organic and nutrient pollution due to return flows from industrial effluent and municipal wastewater. Comparison between upstream and downstream sites shows an increase of salinity and COD concentrations as well as a more sulphate-rich and chloride-rich composition of the downstream waters. The application of box plots, the Seasonal Mann-Kendall Test and the Mann-Kendall Trend in combination show a moderate increase in river water quality due to the reduction of industrial discharges after the collapse of the Soviet Union. However, during this period chloride has a strong decreasing trend which is connected to increased reuse of drainage and return waters. Overall the lower Zerafshan can be described as a collector for water pollutants causing water quality problems for local water supply. The outcomes support the more general debate on Zerafshan water quality with reliable and more detailed information and provide information on water quality issues for the inclusion in the basin efficiency discussions.